CRISPR-Cas9: Transforming Functional Genomics, Precision Medicine, and Drug Development – Opportunities, Challenges, and Future Directions - Khan, Zuber; Mumtaz; Gupta, Sumedha; Mehan, Sidharth; Sharma, Tarun; Kumar, Manjeet; Maurya, Pankaj Kumar; Sharma, Arun Kumar; Das Gupta, Ghanshyam; Narula, Acharan S. (Current Gene Therapy, 2025)
CRISPR-Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats) is a groundbreaking gene-editing technology that enables scientists to make precise changes to the DNA of living organisms. It was first discovered in <span class=
Keywords: gene therapy